Constructing the Antihero: Wade Wilson's Narrative Identity in Deadpool (2016) Through Chatman's Structuralist Framework - Faiq Qodama Almer; Abdillah Nugroho (Lingua Susastra, 2026)
The film Deadpool (2016) presents a distinctive form of heroism that challenges the traditional representation of superheroes as morally ideal and law-abiding figures. This study analyzes how Wade Wilson is represented as an antihero through the film's narrative structure, applying Seymour Chatman's narrative structuralism alongside Prusa's mechanisms of positioning, motivation, and charisma. Employing a qualitative structuralist approach, data were collected through repeated film observation and classification of relevant narrative elements, including character, plot, conflict, and point of view. The findings reveal that positioning operates at the discourse level as a pre-emptive focalization strategy, securing audience alignment through non-linear sequencing and fourth-wall address before story-level moral information is available; motivation is distributed across Todorov’s disruption and recognition stages as a set of causally anchored story events that ground transgression in recognizable human vulnerability; and charisma functions across both levels simultaneously, converting story-level suffering into discourse-level affective appeal through tonal dissonance and metalepsis. Rather than functioning as the co-present cluster Prusa describes, these three mechanisms appear in this film to operate as an ordered reception sequence enabled by the film's discourse-level arrangement: discourse-level positioning prepares the ground on which story-level motivation can be received sympathetically, and charisma consolidates what both have established. On the evidence of a single case we advance this ordering as a hypothesis about how the mechanisms interact, not as a demonstrated law of antihero narrative.